The Effect of Rebound Therapy on Gross Motor Functions in a Child with Spastic Cerebral Palsy: A Case Study - Kora, Alaa Noureldeen; Abdelaziem, Faten Hassan (BioScientific Review, 2020)
Delayed development of the gross motor function abilities is the main manifestation of cerebral palsy (CP) in all children affected by it. Rebound therapy was introduced to help children with different disabilities such as CP. The aim of this case study was to assess the effect of the rebound therapy on the gross motor function abilities in a child with spastic CP. An eight year old girl with spastic CP of Level I on the gross motor function classification system (GMFSC) and graded 1 on the Modified Ashworth Scale (MAS) was selected to undergo the rebound therapy program using mini trampoline. Gross motor abilities were assessed pre- and post- rebound therapy program. The program was conducted for three successive months - three times / week for half an hour / session. The comparison of pre- and post- treatment results showed that rebound therapy improved the total gross motor function abilities by 3.8%, the sitting function by 5%, the kneeling and crawling functions by 3%, the standing function by 2.7% and the walking, running and jumping functions by 8% in a child with spastic CP. Rebound therapy was effective in improving gross motor function abilities in a child with spastic CP. However, further randomized control trials are recommended. Copyright(c) The Authors